The Paradox of Social Media: The De-democratization of Malaysia - Agustino, Leo; Mohamed@Bakar, Badrul Azmier (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2015)
AbstractToday, social media is perceived as the media. Blogs and bloggers have changed journalism; YouTube has discovered rare and raw talents; and the trinity (Facebook, Twitter, YouTube) have sparked revolutions. Focusing on end-users instead of producers and its interactive-ness are two paramount characters that permit ordinary people to engage in extra-ordinary activities. From the showbiz to politics, social media has left its marks. The World political events in recent years, in particular Arab Spring of MENA (Middle East and North Africa) have showcased positive link between social media and democratization. Malaysia has experienced quite a similar phenomenon to MENA in the verge of the 12th General Election (GE-12), held on March 8, 2008. The failure of the only ruling coalition, Barisan Nasional (National Front, or BN) to retain its two-third majority in the GE-12 is an empirical evident of people‟s desire and aspiration for free and fair elections, good-governance, and democratization which are very different from race-based politics. At a glimpse, the results of the 13th General Election (GE-13) which was held on May 5, 2013 are quite similar to the GE-12. Yet, deeper analyses indicated race-base politics and “strong government” has made a comeback. Hence, this article explores the paradox when the state is not only interfering but also participating in social media. This exploration demonstrates social media is not only meant for the masses; and that by possessing money, machinery, and authority; the state is potentially dominant at social media. Keywords: Democratization, de-democratization, social media, general election AbstrakSaat ini, media sosial diterima sebagai media. Blog dan para blogger mengubah jurnalisme: YouTube menemukan bakat-bakat terpendam dan alami; serta the trinity (Facebook, Twitter, YouTube) telah memicu revolusi. Fokus yang lebih diberikan kepada pengguna akhir ketimbang produsen dan karakter interaktifnya adalah dua karakter penting yang memungkinkan orang-orang biasa terlibat dalam aktivitas-aktivitas yang tidak biasa. Dari pertunjukan ke politik, media sosial telah meninggalkan jejaknya. Peristiwa politik dunia dalam beberapa tahun terakhir, khususnya fenomena Arab Spring dari MENA (Timur Tengah dan Afrika Utara) telah menunjukkan hubungan positif antara media sosial dan demokratisasi. Malaysia mempunyai pengalaman yang hampir sama dengan fenomena MENA dalam Pemilihan Umum ke 12 (GE-12), pada 8 Maret 2008. Kegagalan dari satu-satunya koalisi yang berkuasa, Barisan Nasional (National Front, or BN) untuk mempertahankan 2/3 suaranya adalah bukti empiris bahwa rakyat berkeinginan dan mempunyai aspirasi untuk Pemilu yang bebas dan adil, pemerintahan yang baik, dan demokratisasi yang sangat berbeda dari politik berbasis ras. Sekilas, hasil Pemilihan Umum 13 (GE-13) yang diselenggarakan pada 5 Mei 2013 sangat mirip dengan GE-12. Namun, analisis yang lebih dalam menunjukkan bahwa politik berbasis ras dan pemerintah kuat telah kembali. Oleh karena itu, artikel ini mengeksplorasi hal yang paradoks ketika negara tidak hanya mencampuri tetapi juga berpartisipasi di media sosial. Eksplorasi ini menunjukkan bahwa media sosial tidak hanya dimaksudkan untuk massa; dan bahwa dengan memiliki uang, mesin, dan otoritas; negara berpotensi menjadi dominan di media sosial. Kata-Kata Kunci: Demokratisasi, de-demokratisasi, media sosial, pemilihan umum